BETWEEN SHARIA PROHIBITIONS AND LEGAL VACUUM: Islamic Law and State Perspectives As Guidelines In Interfaith Marriages - Nisrina Ismarani; Dhini Nurhasanah Kusuma Putri; Nadhirah Syaharani; Yunisa Akhiryani; Zahra Nurjanah; Indah Sari (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2025)
The prevalence of interfaith marriages in Indonesia has become a serious issue and has attracted significant public attention. Islamic law clearly prohibits interfaith marriages, but this differs from state law, causing a conflict of views among the public. This study aims to determine the reasons why Islamic law prohibits interfaith marriage, to understand why the state does not legalize interfaith marriage, which creates a legal vacuum, and to analyze how the two perspectives, namely Islamic law and state law, address the issue of interfaith marriage. The research method used is qualitative research with a literature study approach, using data obtained from Google Scholar from 2020 to 2024 and other sources such as the Qur'an, applicable laws and regulations, scientific journals, and news articles discussing interfaith marriage. The results of the study show that state law leaves the validity of marriage to the religious laws of each party through Article 2 paragraph (1) of the Marriage Law. Meanwhile, Islamic law strictly prohibits interfaith marriage as stipulated in Article 40 letter (c) and Article 44 of the Compilation of Islamic Law (KHI). Thus, there is a common ground between Islamic law and state law, namely that both place religious norms as the basis for determining the validity of marriage, so that interfaith marriage cannot be legalized in practice.